2018
DOI: 10.1242/jeb.188482
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and dehydration effects on metabolism, water uptake, and the partitioning between respiratory and cutaneous evaporative water loss in a terrestrial toad

Abstract: Terrestrial anurans often experience fluctuations in body temperature and hydration state, which are known to influence evaporative water loss through the skin (EWL Skin ) and lungs (EWL Resp ). These effects arise from associated changes in skin permeability, metabolism and lung ventilation. Herein, we determined the rates of EWL Skin and EWL Resp in the terrestrial toad Rhinella diptycha at different temperatures and hydration states. We measured oxygen uptake rates to verify whether alterations in the parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 75 publications
1
8
0
Order By: Relevance
“…Other studies that have tested for plastic changes in cutaneous water loss rates generally found that lizards or snakes acclimated to drier environments or water restricted environments can adjust cutaneous water loss rates within days or weeks of exposure (Kobayashi et al 1983;Kattan and Lillywhite 1989;Moen et al 2005but see Neilson 2002Gunderson et al 2011). Reduction of cutaneous water loss rates is also well documented in anurans exposed to chronic water deprivation Senzano and Andrade 2018). It is generally accepted that the skin resistance to water loss depends mainly on the intracellular lipid content and ultrastructure of the mesos layer of the epidermis (reviewed by Lillywhite 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies that have tested for plastic changes in cutaneous water loss rates generally found that lizards or snakes acclimated to drier environments or water restricted environments can adjust cutaneous water loss rates within days or weeks of exposure (Kobayashi et al 1983;Kattan and Lillywhite 1989;Moen et al 2005but see Neilson 2002Gunderson et al 2011). Reduction of cutaneous water loss rates is also well documented in anurans exposed to chronic water deprivation Senzano and Andrade 2018). It is generally accepted that the skin resistance to water loss depends mainly on the intracellular lipid content and ultrastructure of the mesos layer of the epidermis (reviewed by Lillywhite 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Ectotherms may also respond to water restriction by thermal depression, that is, the lowering of their preferred set temperature (Ladyman and Bradshaw 2003;Köhler et al 2011; Andrade 2017). This is because higher body temperatures are associated with stronger respiratory and cutaneous water loss rates during activity (e.g., Oufiero and Van Sant 2018;Senzano and Andrade 2018). Previous studies focused mostly on one of these acclimation mechanisms, and their prevalence or pace has been little investigated so far, especially in dry skinned ectotherms.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for those cases in which the information could be recovered, we collected and reported all the components necessary for calculating R s , even though we have not added it as a separate variable in the dataset (Kearney & Porter, 2020). Note that there are potential caveats with respect to this approach because of unknowns in the regional variation of skin and body temperatures (Barroso et al, 2016), difficulties in partitioning sub‐components of EWL (Senzano & Andrade, 2018), and further study or species‐specific features that make it difficult to calculate Rs (Mautz, 1982).…”
Section: Methods and Datasetmentioning
confidence: 99%
“…Thus, for example, a highly effective immune response to pathogens that enter the body might relax selection for barriers on the skin. Additionally, it is important to remember that the skin has many other functions, such as respiration, regulating water flow and as the location of toxin‐excreting glands (Blennerhassett et al, 2019; Huang et al, 2016; Kosmala et al, 2020; Senzano & Andrade, 2018).…”
Section: Discussionmentioning
confidence: 99%